Comparison of boiling, steaming, air frying, deep frying, microwaving and oven-cooking on quality characteristics of keropok lekor (Malaysian fish sausage) - MOHD TAMSIR, MARINA; Ramli, Nurul Shazini; Mahmud Ab-Rashid, Nor Khaizura; Shukri, Radhiah; Ismail Fitry, Mohammad Rashedi (Malaysian Society of Applied Biology, 2021)
Keropok lekor (KL) (Malaysian fish sausage) is usually boiled and then deep-fried for consumption. The combination ofthese cooking methods could produce greasy and fatty products thus negatively affect health in a long term. Other cookingmethods could be better alternatives to the common methods. Therefore, this study aimed to investigate the effect of sixcooking methods namely boiling, steaming, air frying, deep-frying, microwaving and oven-cooking on the KL quality. Thecooked samples were analysed for the moisture, fat, linear expansion, cooking yield, water holding capacity, colour, textureand sensory properties. Boiling showed the highest linear expansion (3.02%), cooking yield (104.10%) and water holdingcapacity (41.04%). Meanwhile, deep frying significantly reduced (p<0.05) the moisture (39.83%) and increased the fat(6.58%) contents, exhibited harder texture (93.13N) and showed a higher yellowness value (8.23) compared to other cookingmethods. No significant difference (p>0.05) was found in other properties; however, panellists significantly (p<0.05) preferredthe crispiness and overall acceptability of the deep-fried followed by oven-cooked KL. Indeed, textures and colours hadsignificant (p<0.05) relationships with sensory properties. In conclusion, deep-frying and oven-cooking reduced the moisturecontent and increased the hardness of KL, which increased the panelists’ preferences. However, deep-fried KL had a higherfat content due to the cooking with oil; therefore, the oven-cooked KL can be the healthier alternative.